Adaptive finite-time control for quadrotor UAV with time-varying load based on disturbance observer - Xiaojing1 WU; Wenyan1 ZHENG; Xueli12 WU; Ran1 ZHEN; Shikai1 SHAO (Journal of Hebei University of Science and Technology, 2021)
For the quadrotor unmanned aerial vehicle (UAV) system with time-varying load,the compound finite-time control strategy was proposed in the presence of unknown external disturbances and unknown drag coefficients.Firstly,a complete mathematical model of quadrotor UAV was established by Newton-Euler method .An adaptive trajectory tracking controller with unknown drag coefficient was designed by combining the adaptive parameter correction method of position loop with backstepping control to estimate load.Then,a finite-time sliding mode controller and Lyapunov stability theory were used so that the position loop and the attitude loop were proved to be asymptotically stable and finite-time stable,respectively.Finally,it was verified by numerical simulation.The results show that the proposed controller improves the system convergence rate,and reduces the influence of outside disturbance to the system.This method overcomes the limitations of known drag coefficients and load in the existing research,improves the anti-interference ability of the system,and has certain reference value for enhancing the practical application of the quadrotor UAV.